Distinguishing Six Edible Berries Based on Metabolic Pathway and Bioactivity Correlations by Non-targeted Metabolite Profiling - Suh, Dong Ho; Jung, Eun Sung; Lee, Gyu Min; Lee, Choong Hwan (Frontiers in Plant Science, 2018)
Berries have been used as valuable sources of polyphenols for human health; however, injudicious uses of berries are widespread without regard to the specific metabolite constituent of each berry. We classified 6 different edible berries (honeyberry, blueberry, mandarin melonberry, mulberry, chokeberry, and Korean black raspberry) based on their metabolite distributions in biosynthetic pathways by non-targeted metabolite profiling and bioactive correlation analysis. Principal component analysis revealed a distinct clustering pattern of metabolites for each berry. Metabolic pathway analysis revealed different biosynthetic routes of secondary metabolites in each berry. Mandarin melonberry contains a relatively higher proportion of genistein, genistein glycoside, and genistein-derived isoflavonoids and prenylflavonoids than the other berries. Various anthocyanin glycosides, synthesized from dihydroquercetin and cyanidin, were more abundant in chokeberry and honeyberry, whereas high levels of flavonoid-and anthocyanins-rutinoside forms were observed in Korean black raspberry. The levels of anthocyanins derived from dihydromyricetin were high in blueberry. The highest anti-oxidant activity was observed in chokeberry and Korean black raspberry, which is positively related to the proportional concentration of flavonoids, phenolics, and anthocyanins. The lowest sugar contents were observed in Korean black raspberry, highest acidity in honeyberry, and lowest acidity in mandarin melonberry, which were specific characteristics among the berries. Taken together, biosynthetic pathway and physicochemical characteristics analyses revealed that the different synthesized routes of flavonoids and anthocyanins and associated bio-activities may be distinct features in each berry and explain their phenotypic diversity at the molecular level.